Human Freedom and the 'Reality of Society': Origins and Development of Karl Polanyi's Ideas during the Interwar Period - Thomasberger, Claus (History of Economic Thought, 2005)
Karl Polanyi's most famous book, The Great Transformation, contains several ideas and theoretical notions which are at the heart of long-lasting controversies throughout the social sciences. Categories such as "double movement," "embeddedness," "disembedding," "market society," or "social freedom" have proved to be fruitful notions not only in anthropology, but also in sociology, political sciences, and economic history. The recent three volume publication of Karl Polanyi's writings during the interwar period–including published articles and unpublished manuscripts–opens for the first time the possibility to have a closer look at the origins and the development of some of Polanyi's concepts during the interwar period. In the paper titled "Human Freedom and the Reality of Society–Origins and Development of Karl Polanyi's Ideas during the Interwar Period," Claus Thomasberger addresses Polanyi's idea of a polar relationship between human freedom and the "reality of society." The paper offers new insights, discussing central questions which are crucial to the understanding of Polanyi's reasoning: Where are the roots of his central categories? What influence did Marx have on Polanyi's thinking? What is the relationship between Polanyi's approach and the Austrian School of Economics? Is it appropriate to read his work in terms of an institutional approach? In order to give an answer to these questions, the paper goes back not only to the 1930s, but to the 1920s as well. As it demonstrates, Polanyi had already developed the core ideas of his thinking in Vienna, participating actively in the discussions between the Austrian School of Economics and Austro-Marxism about the possibilities of a socialist society.
Economics; Philosophy
Keywords: history of economic thought: individuals; reality of society

Massacre of the Doves?: Interpreting Israel's 2003 Elections - McMahon, Sean F. (British Journal of Middle Eastern Studies, 2005)
This article argues that Israel's 2003 elections are best understood as a deeper embedding of neoliberalism in the Israeli polity. It is argued that the most accurate characterization of the elections is as an articulation of Polanyi's Phase I of the double-movement. The argument is developed in four stages. First, the Israeli elections are understood as a local reaction to the multilayered processes of globalization. The Israeli state and its elections are located in the neoliberal ideology which underwrites the phenomenon broadly defined as globalization. Second, the election results are reviewed. Third, the dominant interpretations of the elections are critically examined. Specifically, representations of the elections as a defeat of the parties of peace and as a rebuke of Sephardim/ultra-Orthodox influence in Israeli government are interrogated. Fourth, the coalition negotiations of February 2003, the constitution of Israel's 30 th government and some of the initiatives undertaken by Finance Minister Benjamin Netanyahu are explicated through deployment of Polanyi's double-movement framework.
Political Science; Area Studies
Keywords: Israel - politics and government; double movement; elections; globalization; neoliberalism

Fighting standards with standards: harmonization, rents, and social accountability in certified agrofood networks - Mutersbaugh, Tad (Environment & Planning A, 2005)
In this paper I explore the remaking of globalized standards through harmonization, and its impact upon certified-organic and fair-trade agrofood networks. I focus on certification standards and discuss four shifts associated with globalized standards (an increased importance of multilateral institutions, changes to standards language, displacement of network-specific standards, and a shift away from relational standards). It is then argued, with reference to value-chain rent theory, that the shift to globalized standards has transformed rent relations in ways that benefit certain actors (that is, retailers) and imperil the earnings of others. In brief, globalized standards increase the costs of standards compliance, the full burden of which falls upon immiserated producers, to the point at which farmers see little economic advantage to certified-organic and fair-trade production. I then examine social-accountability standards that seek to `fight standards with standards' by championing the consolidation of strong labor and environmental protections under a single label. The study suggests that a single-label strategy can be successful, yet must struggle to overcome a Polanyian double bind, for, in order to build broad coalitions necessary to extend the reach of protective standards, the coalitions must include corporate interests that prefer weaker, contract-based standards.
Geography
Keywords: agricultural accounting; agricultural industries; applied ecology; environmental policy; retail industry; retail stores

Polanyi, Chayanov, and Lessons for the Study of the Informal Sector - Özveren, Eyüp (Journal of Economic Issues (Association for Evolutionary Economics), 2005)
This article offers an alternative institutional economic approach to the informal sector by interpreting the works of economists Karl Polanyi and Alexander Vasil'evich Chayanov. Far from withering away, the informal sector continues to occupy an important place within economies in general and within the so-called developing economies in particular. Relatively speaking, the informal sector is inferior and more spontaneous, if not actually incomplete. Within the informal sector there are numerous small competitive firms, free entry, market-determined factor and product prices, together with a concentration of petty retail and services, labor-intensive production processes, and low productivity. According to Polanyi, one major drawback of mainstream economics is the insistence that the market mode is synonymous with the economy, and, under the weight of this assumption, formalistic economic analysis is assumed to be universally applicable to the study of all times and places. As a consequence, mainstream economists see markets where there are none.
Economics
Keywords: CHAYANOV; Alexander V.; POLANYI; Karl; 1886-1964; economic sectors; economics; informal sector (economics); labor productivity; labour productivity; small business

The role of the UN Millennium Declaration and of the World Economic and World Social Forum for Structural Change - Abrahamson, Hans (Conference Papers – International Studies Association, 2005)
Globalisation can in a polanyian sense be understood as a double movement. Societal reaction to the shortcomings of the corporate driven process of globalisation from above (the first movement) creates a counter movement from below (the second movement). The relations between different actors within the political landscape and the area of tensions between the two movements are characterised by the gramscian war of position and its power struggle over the hegemonic discourse. At times the constellation of political forces permits an institutionalised state of equilibrium built on converging interests between different social forces. During the Westphalia era with its nation-state project the social contract constituted the base for such an historic compromise. The end of the cold war and strengthened process of corporate globalisation has eroded the base for this social contract on a national level increasing development gaps not only between countries but also within countries. This paper addresses the question of room for manoeuvre for structural change in order to deal with present challenges within the Global Political Economy. It discusses how possibly the UN Millennium Declaration could be used in the ongoing discursive war of position between actors at the World Economic Forum in Davos (representing the first movement) and actors at the World Social Forum in Porto Alegre (representing the second movement) in order create a social base for a new social contract albeit on the global level. Such a discussion also illustrates present potential of these arenas in contributing to a future global political economy of peace and development.
Peace Studies; Development Studies
Keywords: United Nations; World Economic Forum; economics; forums (discussion & debate); globalization; hegemony; political science

Bridging boundaries and Mending Fences? Finding "community" in transboundary conservation approaches - Hoon, Parakh (Conference Papers – International Studies Association, 2005)
The article presents the conference paper titled "Bridging boundaries and Mending Fences? Finding community in transboundary conservation approaches" prepared for the "Annual Convention of the International Studies Association" held in Honolulu, Hawaii. It discusses the implementation of the Community Based Natural Resource Management in Botswana in early 1990s. It examines the contemporary applications of the idea of embeddedness which was coined by intellectual Karl Polanyi as an analytical and ideological foil to the notion of self-regulating markets.
Political Science
Keywords: Botswana; conservation of natural resources; conservation projects; international relations; self-regulating market

Gramsci, Polanyi and Impressions from Africa on the Social Forum Phenomenon - Bond, Patrick (International Journal of Urban and Regional Research, 2005)
The rise of the Social Forum phenomenon has been heartily welcomed, partly so as to unite diverse discourses of anti-neoliberal and anti-imperialist resistance under a common banner. There are debates worth flagging, however, that draw our attention to political philosophies (typically binary statist versus anti-statist disputes), visions of agency (typically networked movements versus parties), and potentials for revolutionary processes to emerge within ‘civil society’. In the spirit of Polanyi, many South Africans and other Africans are working on ‘decommodification’ strategies that range from particular sites of project-level struggles to national, regional and international advocacy. But we must be conscious, as well, of warnings by Gramsci about the long march through a civil society often co-opted to support state and neoliberal projects. The merits of African intellectual engagements with radical social movements have been shown in sites such as South African cities, but the African Social Forum awaits further opportunities to welcome allied researchers and academics. As the World Social Forum comes to Africa in 2007, Marcuse’s hope that the constituent movements begin to coalesce around a program is timely. However, this is likely to emanate more from intra-sectoral networks rather than from multidisciplinary moments such as the WSF itself. La montée du phénomène des Forums sociaux a été accueillie chaleureusement, en partie comme manière d’unifier sous un même drapeau les multiples discours de la résistance anti-néolibérale et anti-impérialiste. Certains débats éminents attirent pourtant l’attention sur des philosophies politiques (généralement des oppositions binaires étatistes/anti-étatistes), des visions de l’intermédiation (en général, mouvements interconnectés/partis) et des processus révolutionnaires susceptibles de naître au sein de ‘la société civile’. Dans l’esprit de Polanyi, nombre d’Africains, du Sud et d’ailleurs, s’emploient à des stratégies de ‘démarchandisation’ couvrant à la fois sites de conflit particuliers liés à un projet et plaidoyers aux niveaux national, régional et international. Toutefois, il ne faut pas oublier les avertissements de Gramsci pour qui la longue marche passant par la société civile risquait d’être cooptée afin de soutenir des projets gouvernementaux ou néolibéraux. Si les engagements d’intellectuels africains aux côtés de mouvement sociaux radiaux se sont révélés bénéfiques dans des cas tels que les villes d’Afrique du Sud, le Forum social africain espère d’autres occasions de rallier chercheurs et universitaires. Comme le Forum social mondial se tiendra en Afrique en 2007, l’espoir de Marcuse — de voir les mouvements constitutifs s’unir progressivement autour d’un programme — est d’actualité. Cependant, cette évolution viendra plus probablement de réseaux intra-sectoriels que d’élans multidisciplinaires comme le FSM.
Geography; Political Economy
Keywords: GRAMSCI; Antonio; 1891-1937; South Africa; decommodification; development studies; geography; social forum phenomenon

From flows to violence - Kalb, Don (Anthropological Theory, 2005)
Recent globalization theory reflected a chain of world historical events since the end of the Cold War. Globalization theories were tools for the making of political alliances between market liberals and political, liberals. From the mid-1990s a broad range of institutionalist social science programs showed that globalization outcomes were often better explained by institutional logics (including cultural ones) than by global flows per se. This is, among others, illustrated by the debate on global inequality data. The emerging debate on empire and imperalism is discussed as a logical offshoot of the globalization discussion just as the phenomenon itself is seen as a likely outcome of an epoch of market-driven globalization. Globalization was predicated on the emergence of a US-led transnational western state structure on behalf of the transnational capitalist class based in finance and the large corporations. Territory and space have become more important rather than less, but the explanation of regional trajectories must now be located more firmly in the interaction between local and global structures. This leads to a new agenda in the social sciences: one oriented toward common interdisciplinary programs with a limited range of core questions - about state formations, class formations, mobilizations, claim making, and associated cultural processes. Programs should be more theory driven, comparative, and in search of explanations of divergent spatial and temporal outcomes of universal process.
Anthropology
Keywords: alliances (international relations); civilization; cultural policy; dual polarization; empire; globalisation; globalization; imperialism; international relations; social sciences & state; transnational capitalist class

Beyond Boganism - Brown, Beth; Brown, Doug (Journal of Popular Culture, 2005)
The article analyzes the global economy by subjecting it to an interpretive scheme derived from popular culture Boganism, an Australian colloquialism or street slang used by teenagers. Boganism, the social phenomenon of being both unaware and irresponsible, is the result of a particular type of human abandonment. This abandonment is linked to the new hypercapitalism of globalization. The article will establish the structural roots of boganism, examine the case of the abandonment of U.S. youth, and conclude with reform recommendations necessary to shift us beyond boganism to a culture of sustainability. Karl Polanyi, a Hungarian economist, argued a half century ago that the birth of capitalism meant the emergence of what he called the disembedded economy. Polanyi's essential problem with capitalism, when it emerged in the sixteenth century, was that it creates a society in which everyone is dependent on markets to meet their basic needs. The pace of life has clearly increased with the maturation of capitalism and industrialism. But with the high-technology revolution, accompanied as it has been by the globalization of capitalism, what is happening is acceleration of everyday life, the economy, market transactions, and much more. Stratification: relationships of supra- and subordination, relations of domination and injustice. These are the social dimensions and institutional, structural relations between people and groups that have played defining roles in social, political, and economic analysis over the last three centuries of industrialism. Categories of stratification include classism, racism, statism, and sexism, and others. Along with these, we can add boganism.
Political Science; Economics
Keywords: capitalism; disembedded economy; disembeddedness; globalization; popular culture; socioeconomics

Labour and Globalization: Towards a New Internationalism? - Ramasamy, P. (Travail et Mondialisation: Vers un nouvel internationalisme?, 2005)
A one-dimensional view of capitalism inevitably leads to the conclusion that labour is in a state of deep crisis. However, if we examine globalization as a contradictory process, then it is possible to regard its relationship with labour as a transformative one. In this context, the decline of trade union density in developed countries and the rise of new forms of trade unionism in selected countries of the South, illustrate the contradictory relationship between labour and capital. In accordance with Marx, capitalist expansion not only does away with old forms of labour organizations, but has the tendency to create new forms of labour resistance. Similarly, Polanyi argues that attempts to disembed the economy (return to free market enterprise) from the rest of society will be resisted by societal forces. (English)
Political Science
Keywords: capitalism; developed countries; embeddedness; free enterprise; globalization; international trade; labor; labor unions; labour; labour unions; political doctrines

Economics and the Space of Modernity: - Escobar, Arturo (Cultural Studies, 2005)
This text was the original second chapter of the author's doctoral dissertation (Escobar 1987); this chapter was never included in the book that eventually grew from the dissertation (Escobar 1995). Although the chapter's contribution to debates on the economy are largely synthetic and certainly not original, the author wanted to publish it for a number of reasons. First, the alleged triumph of neo-liberal ideologies and the increase in depth and scope of market cultures at present make even more important the task of cultural analysis of economics and the economy. This paper was an effort in this direction, particularly to mapping the genealogies of what in the paper is called ‘the Western economy’. Second, there have been some recent claims that the cultural analysis of economics and the economy has hardly been broached. References to Polanyi's foundational role in this respect are, of course, de rigueur, but one only needs to point at the pioneering work of Stephen Gudeman since the 1980s to dispute this claim. Third, the same cultural analysis is experiencing a much needed surge, with several groups today fully engaged with it from various – some times overlapping – perspectives. Finally, the impetus for this piece also comes from the creative efforts by a number of social movements in the world – such as some of the autonomistas in Argentina – to go even beyond ‘rethinking’ the economy to propose that what is needed is a new invention altogether.
Anthropology; Cultural Studies
Keywords: anthropology of modernity; cultural studies; cultures of economy; economic history; economics; genealogy; modernity; resistance; social history; third world

The fruits of intellectual production: economic and scientific specialisation among OECD countries - Laursen, Keld; Salter, Ammon (Cambridge Journal of Economics, 2005)
This paper brings together data from 17 OECD countries on scientific publications, patents and production, to explore the relationship between scientific and economic specialisation for 17 manufacturing industries. Since Marx, there has been a fundamental debate in economics about the link between science and the economic system. Marx argued that the needs of production shape scientific developments and that science has become a factor of production, whereas Polanyi argued that developments in science are largely independent of the economic sphere. Using a panel data model and econometric estimations at the industry level, the paper derives some hypotheses from the two positions and finds that, while the overall evidence on the link between national production and scientific specialisation is mixed, it is important to have high levels of relevant to-the-industry scientific strength per capita in order to be specialised in science-based industries.
Economics
Keywords: bibliometric data; econometrics; industries; international economic specialisation; manufactures; manufacturing industries; patent laws & legislation; patent suits; science & industry; scientific specialisation

Engendering Charismatic Economies: Pentecostalism, Global Political Economy, and the Crisis of Social Reproduction - Barker, Isabelle V. (Conference Papers – American Political Science Association, 2005)
Pentecostalism is the fastest growing religion in the world today. A number of explanatory theories exist, but in this paper, I hone in on the nexus between economic restructuring and Pentecostalism to explore this extraordinary expansion. Bringing together the work of feminist political economists and of Karl Polanyi, I argue that neo-liberal globalization threatens mechanisms for meeting social reproductive needs. Neo-liberalism cannot meet these needs on its own, and I suggest that Pentecostalism addresses these gaps, effectively embedding neo-liberal economic policies. It does so by facilitating norms and practices on the part of individual adherents to provide for the care work required for human reproduction; to adopt norms required of a neo-liberal labor force; and, to embrace the kind of transnational social identity that is compatible with labor migration and global markets. ..PAT.-Conference Proceeding
Political Science
Keywords: CHRISTIANITY; GLOBALIZATION; Globalization; PENTECOSTALISM; Pentecostalism; Polanyi; Karl; 1886-1964; RELIGION & sociology; feminism; feminist political economy; neo-liberalism; social reproduction

José Bové and the Globalisation Countermovement in France and Beyond: A Polanyian Interpretation - Birchfield, Vicki (Review of International Studies, 2005)
This article illustrates the continuing salience of Karl Polanyi's The Great Transformation (1944) by employing two of its central concepts, fictitious commodities and the double movement to interpret the globalisation countermovement and one of its most important figures, José Bové. I explain the transformation of José Bové from rural sheep farmer to French folk hero and global activist and analyse the extent to which his rhetoric and political actions are congruent with Polanyi's key insights. Arguing against the media characterisation of Bové as protectionist, I show that this misrepresentation conceals the larger ideological threat his movement poses to institutionalised politics and neoliberal hegemony. The political vision underlying Bové's symbolic media tactics and articulated in his book, Le Monde n'est pas une Marchandise, reveals significant manifestations of Polanyi's chief intellectual legacy - an unparalleled critique of economism and market society. An often neglected question in Polanyian scholarship is whether or not it is possible to have a market economy without becoming a market society. A more careful analysis of Polanyi's thought sheds light on this key issue while the empirical analysis of Bové's movement reveals its implications for French society and the broader globalisation countermovement.
Political Science
Keywords: capitalism; commodities; countermovement; economic globalization; economic liberalism; free market economies; globalization; international economics; political movements; social movements

Karl Polanyi et la séparation institutionnelle entre politique et économie - Buğra, Ayşe (Raisons politiques, 2005)
This article explores Karl Polanyi’s analysis of the institutional separation of politic and the economy in the context of the 19th century market economy. The contribution his analysis could make to the quest for viable alternatives to the contemporary neo-liberal international order depends on how we construe two key concepts in his work, “disembeddedness” and “countermovement”. In this regard the author suggests that: 1) In Polanyi’s work the disembedded economy appears not as a sociological reality but as a political project, and 2) Polanyi’s analysis of the countermovement does not justify all types of resistance to the market economy as humane and politically acceptable.
Economics; History
Keywords: institutional separation

Two heterodox economists: Neurath and Karl Polanyi - Giandomenica, Becchio (MyScienceWork Working paper No. 11/2005 Università di Torino 1, 2005)
This paper is based on the idea that between the 1920s and the mid-1930s in Vienna there were two forms of heterodox economic theory: the Austrian economic school headed by Ludwig von Mises and another interesting form of heterodox economics opposed to the Austrian school (above all politically) and pursued by various social thinkers (Otto Neurath, Karl Polanyi, Otto Bauer, Felix Schaffer, Felix Weil, Jacob Marschak). They were engaged in the debate on the possibilities of a planned economy: Austrian socialist economists proposed a sort of ‘third’ way between pure capitalism (whose Viennese stronghold was the Austrian economic school) and orthodox communism à la Kautzsky (deeply rooted in Germany). This paper focuses on the affinities between Neurath and Polanyi’s economic thought: despite some major differences between them, they shared a common philosophical background on which they founded their heterodox economic theory. After a brief historical premise, there is a first part, which deals with the debate on a planned economy and a second part, which deals with the influence of Neurath on the Polanyi’s vision of the faults of the neoclassical economic theory: the concepts of “disembedded economy” and of the so-called “economicistic fallacy”. NEURATH AND POLANYI IN VIENNA Neurath described himself as a ‘social engin
Economics; Philosophy
Keywords: Austrian economic school; NEURATH; Otto; economics; heterodox economics; philosophy; political science

Le port de commerce : un concept en débat - Graslin, Laetitia; Maucourant, Jérôme (Topoi, 2005)
Economics; History
Keywords: Dahomey and the Slave Trade; port of commerce

A New Middle East? Globalization, Peace and the Double Movement - Guy Ben-Porat (International Relations, 2005)
The rise and fall of the New Middle East (NME) cannot be separated from wider global developments and must therefore be studied in relation to them, in both their ideational and material aspects. The ideological background of the NME has drawn upon the ideology of globalization and shares its underlying tenets of rationality, professionalism and virtues of market economy. In the early 1990s a discourse of globalization was set in motion, highlighting economic and technological development that supposedly rendered territory and territorial disputes marginal or irrelevant. The NME, supported by Israel's business, political and academic elites, advocated liberal economics and peace as a solution to the region's problems. But Israeli elites have failed to turn the idea of the NME into a hegemonic concept, as this attempted liberal hegemony invoked a Polanyian double movement that undermined the peace process. The scenario of the NME and the trade-off between territorial integrity and promised regional prosperity not only met fierce ideological rejection, but, perhaps more importantly, failed to persuade the many more skeptics. Limited in its appeal and lacking sufficient legitimacy, the peace process was exposed to derailment by extremists, locking the region into cycles of violence.
Political Science; International Relations
Keywords: Middle East; capitalism; double movement; economic development; globalization; ideology; international relations

Le troc et la monnaie dans la pensée de Polanyi - Maucourant, Jérôme (2005)
Relire K. Polanyi nous affranchit d'une double illusion. Selon la première, l'homme est essentiellement un atome utilitaire exploitant les gains supposés de l'échange, cette vieille « fable du troc » n'étant pas remise en cause par l'économie des « coûts de transaction ». La seconde illusion, construction hétérodoxe voulant s'affranchir de cette fable, attribue à la monnaie les traits d'une institution aussi transhistorique qu'universelle. Certes, de nombreux phénomènes qualifiés de « troc » sont en réalité issus de la destruction d'ordres monétaires. D'ailleurs, K. Polanyi, commentant Aristote, montrait déjà que le dogme de la naturalité du troc est une projection des a priori de la société de marché. Mais, ceci ne signifie pas que la monnaie soit « souveraine » : seules les communautés politiques sont souveraines, seule la réciprocité, au sens de l'école maussienne, est un universel, le troc pouvant être « enchâssé » dans l'économie. Review Polanyi frees us a double illusion. According to the first, man is essentially a utilitarian atom exploiting the supposed gains of exchange, this old "barter fable" not being called into question by the economy of "transaction costs". The second illusion, a heterodox construction wishing to free itself from this fable, attributes to money the features of an institution as transhistorical as a universal one. Certainly, many phenomena called "barter" are in fact derived from the destruction of monetary orders. Besides, K. Polanyi, commenting Aristotle, already showed that the dogma of the naturalness of barter is a projection of a priori of the market society. But this does not mean that money is "sovereign": only political communities are sovereign, only reciprocity, in the sense of the Maussian school, is a universal, barter can be "enshrined" in the economy.
Economics; Political Science
Keywords: barter; universal barter

L'ère de l'opulence selon Polanyi - Maucourant, Jérome; Vivel, Christel (Economies et sociétés, 2005)
L'article expose la problématique d'un texte peu connu de Polanyi datant de 1959. Prétextant un commentaire de L'ère de l'opulence de Galbraith, il soutient que le naturalisme de l'économie dominante nous interdit de comprendre la signification véritable de la rareté. Polanyi montre alors que les oppositions classiques entre liberté et égalité, économie et démocratie, peuvent être dépassées dans le cadre d'une société nouvelle abolissant la séparation institutionnelle de l'économique et du politique. Ces thèses de Polanyi sont imprégnées d'un aristotélisme tenant compte des déchirures sociales que furent le machinisme et les fascismes. KM: One aims at presenting a unknown Polanyi's text. Starting with a comment of the Affluent Society from Galbraith, we explain that the mainstream economics'naturalism prevents us from understanding the actual significance of scarcity. Polanyi shows that the classical oppositions between liberty and equality, economy and democracy can be overcame in the frame of a brand new society in which the institutional line between economics and politics should be abolished. This is sustained by an aristotelism that takes into account the social breaks produced by machinism and fascisms.
Economics; Sociology
Keywords: opulence; rareté

Propos d'Aristote sur une société d'abondance - Polanyi, Karl (Economies et sociétés, 2005)
KM: Translation of a Polanyi essay - involves Michele Cangiani and Jérôme Maucouran. Nous publions ci-dessous la traduction en français d'un texte inédit de Karl Polanyi : « Aristotle on an affluent society » (13 mars 1959, Archives de l'Institut Karl Polanyi d'économie politique, Montréal). Ce texte doit paraître aux Éditions du Seuil, en 2006, dans un recueil intitulé Essais de Karl Polanyi, sous la direction scientifique de Michele Cangiani et Jérôme Maucourant, dans la collection « Économie humaine » dirigée par Jacques Généreux. La version présente de ce texte a été traduite par Laurence Collaud en collaboration avec Michele Cangiani, Jérôme Maucourant et Christel Vivel. Œconomia remercie les Éditions du Seuil ainsi que Jacques Généreux d'avoir autorisé cette publication. We publish the French translation of an unpublished text by Karl Polanyi: "Aristotle on an affluent society" (March 13, 1959, Archives of the Karl Polanyi Institute of Political Economy, Montreal). This text is to be published by Éditions du Seuil in 2006 in a collection entitled Essays by Karl Polanyi, under the scientific direction of Michele Cangiani and Jérôme Maucourant, in the collection "Économie humaine" directed by Jacques Généreux. The present version of this text has been translated by Laurence Collaud in collaboration with Michele Cangiani, Jérôme Maucourant and Christel Vivel. Œconomia thanks Editions du Seuil and Jacques Généreux for authorizing this publication.
N/A
Keywords: ARISTOTLE; CANGIANI; Michele; MAUCOURANT; Jérôme; translation

The Transition between the Old and New Traditional Economies in India - Rosser, J. Barkley; Rosser, Marina V. (Comparative Economic Studies (Palgrave), 2005)
We extend Karl Polanyi's traditional economy concept to modern economies with advanced technology that are embedded in a traditional socio-cultural framework. This is the New Traditional economy, seen in parts of the Islamic world and with the Hindu nationalist movement in India. However, rural India is also the largest repository of the Old Traditional economy with its Hindu caste and jajmani system of reciprocal labour relations. The changes in India's complexly mixed economy, with its increasing market and strong planned elements, constitute a transition from the Old to the New Traditional economy. We shall consider this transition both ideologically and systemically.
Economics
Keywords: Hinduism; India; caste; economics; labor; labour; markets; nationalism; new traditional economy; old traditional economy; transition

Dé-penser l'économique sans Mauss et avec Polanyi - Sobel, Richard (L'Homme & la société, 2005)
Political Science
Keywords: MAUSS; Marcel; 1872-1950